PROBLEMATIK YURIDIS PEMBUKTIAN TINDAK PIDANA KORUPSI DENGAN MENGGUNAKAN AUDIT KEUANGAN BPK DAN BPKP - Bernatd Jufly; Erdianto '; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Corruption is no longer a crime that can be classified as a conventional crime. As a crime of extraordinary crime, when viewed from the victim, what is generated from this crime is not limited to individuals but the community, nation and state. So this crime has caused a setback for Indonesia. One element of the corruption offense is the